Płeć kulturowa a płeć szamana. Przypadek kultury buriackiej = Gender and the sex of shaman: a case of Buriacki culture - Połeć, Wojciech (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The subject of this article is a reflection on the bonds between the sex of a shaman and the concepts of gender prevailing in the culture in which we meet male and female shamans. Based on notions of differentiation of sexes among shamans, widespread in scientific and popular science literature, the autor`s intention is to show intercultural conditionality of the position of female and male shamans.
Keywords: płeć; transpłciowość; szamanizm; antropologia społeczna; gender; transgender; shamanism; social anthropology